Molecular Docking Studies and ADME-Tox Prediction of Phytocompounds from Lycopersicon esculentum mill. as a Drug Candidate for Alopecia Treatment - Zulpakor Oktoba; Recky Patala; Muhammad Fitra Wardhana Sayoeti; Putu Ristyaning Ayu Sangging; Tri Umiana Soleha (Universitas Lambung Mangkurat, 2026)
Alopecia is a disorder of the hair follicles that causes hair loss, either in limited areas or throughout the entire body. This study aims to evaluate the potential and molecular interactions of compounds found in the Rampai plant (Lycopersicon esculentum Mill.). The Rampai plant is known to contain various secondary metabolites such as alkaloids, flavonoids, arbutin, amygdalin, and pectin, which have the potential to be developed as antialopecia drug candidates through an in-silico approach to androgen receptors (PDB ID: 4K7A) and ADME-Tox profile predictions. The in-silico approach was conducted using the molecular docking method to predict the interaction between the active compounds from the Rampai plant and the androgen receptor using Autodock Tools 1.5.7 and Vina software, while the ADME-Tox analysis was conducted through the pkCSM platform. The molecular docking results showed that the reference ligand (Minoxidil) had an affinity energy of âˆ’7.353 kcal/mol, while the test compound with the best affinity was isorhamnetin with a value of âˆ’8.398 kcal/mol, which was lower (more stable) than Minoxidil. In addition, the ADME-Tox prediction results for isorhamnetin show favorable pharmacokinetic characteristics, especially in terms of skin permeability, absorption and distribution. Thus, isorhamnetin has the potential as an androgen receptor antagonist and a role in the development of therapies for alopecia.